COMMUNITY SERVICE EDUCATION RELATED TO HYPERTENSION IN PREGNANT WOMEN AT THE DELIMA CLINIC - Palupi Bodro Sayekti; Deni Irawati; Sophie Aklesia Agustin (Jurnal Masyarakat Indonesia (Jumas), 2025)
Hypertension in pregnancy is one of the medical complications that is a major challenge in maternal health services, as well as being the main cause of maternal mortality and morbidity nationally and globally. If not detected and managed properly, this condition can be at risk of triggering preeclampsia to premature birth. This community service activity aims to increase the knowledge of pregnant women at the Delima Clinic about the early detection of the risk of hypertension and the importance of managing a healthy lifestyle during pregnancy. The implementation of the activity was carried out on July 23, 2024 by a team of lecturers and students from STIKes Darmo Medan through an interactive counseling method intended for pregnant women and their families as a support system. The results of the evaluation conducted through a comparison of pre-test and post-test showed an increase in participants' understanding of recognizing hypertension symptoms and the importance of adherence to routine health controls. In conclusion, structured education on hypertension management has proven to be effective in empowering pregnant women to take preventive measures independently, so that it is expected to support the creation of healthy and safe pregnancies.